2009
DOI: 10.1089/cap.2008.0105
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Onset Diagnoses in a Case Series of Teens at Clinical High Risk for Psychosis

Abstract: Reasons: Schizophrenia is typically an adult neurodevelopmental disorder that has its antecedents in childhood and adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Only a handful of studies have looked at the presentation of at-risk adolescents [35][36][37][38] excluding studies where risk is solely based on genetic predisposition. In one of the first studies, Meyer and colleagues [36] identified 24 adolescents who reported significant perceptual abnormalities (20/24, 83%), unusual thought content (18/24, 75%) and suspiciousness (13/54%) symptoms at baseline assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Only a handful of studies have looked at the presentation of at-risk adolescents [35][36][37][38] excluding studies where risk is solely based on genetic predisposition. In one of the first studies, Meyer and colleagues [36] identified 24 adolescents who reported significant perceptual abnormalities (20/24, 83%), unusual thought content (18/24, 75%) and suspiciousness (13/54%) symptoms at baseline assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Because young people identified as at risk of psychosis typically have comorbid diagnoses of depression and anxiety (5), one strategy for evaluating the stigma associated with the label of psychosis risk syndrome is to compare it with the stigma attached to labels of depression or anxiety. In national surveys of public attitudes toward adolescents labeled with nonpsychotic disorders such as major depression, 19% to 20% of respondents endorsed rejection, indicating moderately negative social distance, and 31% to 42% of respondents perceived such individuals as violent toward others, indicating moderately negative stereotypes (6,7).…”
mentioning
confidence: 99%
“…A meta-analysis of studies suggests that the large variance in their effect sizes may be related to the effects of moderator variables, and different strategies for ascertainment of both CHR subjects and controls (Moberg et al, 2014). Of note, a pattern of mixed results for SID is evident across many psychiatric disorders in children and adolescents, including attention deficit disorder, autism spectrum disorders, obsessive compulsive disorder and other anxiety disorders (reviewed by Schecklmann et al, 2013), many of which are comorbid diagnoses observed in CHR cohorts, including in the current study (also reviewed in Mazzoni et al, 2009). Of note, our study’s main limitations are its size and the relatively low smell identification ability among community-ascertained controls.…”
Section: Discussionmentioning
confidence: 71%